A Plant-Based Meal Increases Gastrointestinal Hormones and Satiety More Than an Energy- and Macronutrient-Matched Processed-Meat Meal in T2D, Obese, and Healthy Men: A Three-Group Randomized Crossover Study - Klementova, Marta; Thieme, Lenka; Haluzik, Martin; Pavlovicova, Renata; Hill, Martin; Pelikanova, Terezie; Kahleova, Hana (Nutrients, 2019)
Gastrointestinal hormones are involved in regulation of glucose metabolism and satiety. We tested the acute effect of meal composition on these hormones in three population groups. A randomized crossover design was used to examine the effects of two energy- and macronutrient-matched meals: a processed-meat and cheese (M-meal) and a vegan meal with tofu (V-meal) on gastrointestinal hormones, and satiety in men with type 2 diabetes (T2D, n = 20), obese men (O, n = 20), and healthy men (H, n = 20). Plasma concentrations of glucagon-like peptide -1 (GLP-1), amylin, and peptide YY (PYY) were determined at 0, 30, 60, 120 and 180 min. Visual analogue scale was used to assess satiety. We used repeated-measures Analysis of variance (ANOVA) for statistical analysis. Postprandial secretion of GLP-1 increased after the V-meal in T2D (by 30.5%; 95%CI 21.2 to 40.7%; p < 0.001) and H (by 15.8%; 95%CI 8.6 to 23.5%; p = 0.01). Postprandial plasma concentrations of amylin increased in in all groups after the V-meal: by 15.7% in T2D (95%CI 11.8 to 19.6%; p < 0.001); by 11.5% in O (95%CI 7.8 to 15.3%; p = 0.03); and by 13.8% in H (95%CI 8.4 to 19.5%; p < 0.001). An increase in postprandial values of PYY after the V-meal was significant only in H (by 18.9%; 95%CI 7.5 to 31.3%; p = 0.03). Satiety was greater in all participants after the V-meal: by 9% in T2D (95%CI 4.4 to 13.6%; p = 0.004); by 18.7% in O (95%CI 12.8 to 24.6%; p < 0.001); and by 25% in H (95%CI 18.2 to 31.7%; p < 0.001). Our results indicate there is an increase in gut hormones and satiety, following consumption of a single plant-based meal with tofu when compared with an energy- and macronutrient-matched processed-meat meat and cheese meal, in healthy, obese and diabetic men.
Keywords: Insulin; Diet, Vegetarian; Male; nutrition; inzulin; Obesity; dietní proteiny; type 2 diabetes; glykovaný hemoglobin; Dietary Carbohydrates; klinické křížové studie; krevní glukóza; Cholesterol; Gastrointestinal Hormones; Meat Products; obezita; Adult; satiety; Aged; dospělí; Diabetes Mellitus, Type 2; mužské pohlaví; senioři; Dietary Fats; gastrointestinal hormones; postprandiální období; Meals; triglyceridy; diabetes mellitus 2. typu; uspokojení potřeb; dietní tuky; cholesterol; plant-based; lidé; jídla; Glycated Hemoglobin; Humans; Postprandial Period; Body Mass Index; dietní sacharidy; gastrointestinální hormony; dieta vegetariánská; Glycated Hemoglobin A; Triglycerides; index tělesné hmotnosti; Cross-Over Studies; Satiation; Blood Glucose; masné výrobky; lidé středního věku; Dietary Proteins; Middle Aged